Counseling Effect on Smoking Cessation Behavior in Junior High School Students - Amsal Amsal; Kadar Ramadhan; Nurfatimah Nurfatimah; Ahmad Ramadhan; Aminuddin Aminuddin; Fahmi Hafid (Media Kesehatan Masyarakat Indonesia, 2021)
The prevalence of smoking habits among children and adolescents has increased quantitative and qualitative, which further elevates the risk of diseases. Furthermore, the 2014 Global Youth Tobacco Survey (GYTS) (data showed the intention to quit smoking by 88.2% of students, although only 24% received assistance in affiliated programs; hence support is required from the immediate environment. Therefore, the purpose of this research, was to determine the effect of counseling in the success of smoking cessation in junior high school students. The research design used was a prospective cohort. The subjects of this research include all junior high school students with the smoking habit, of which 40 participants were selected. These respondents were provided with smoking cessation counseling for six sessions (4 months). Survival analysis was used to evaluate the data collected. After the six counseling sessions, the cessation success and failure rates were 75% and 25%, respectively. Smoking cessation was related to nicotine addiction (p<0.001; Adj.HR 25.2;95% CI 4.9-129.9) and activeness in counseling (p=0.001; Adj.HR 12.8; 95% CI 2.8-57.9). This research is expected to help students with the smoking habit terminate the practice, subsequently reducing the prevalence in Poso Regency.